AI ALGORITHMS AND MACHINE LEARNING FOR BIG DATA PROCESSING: TRENDS AND PROGRESS - Loso Judijanto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
AI and machine learning algorithms play an important role in big data processing, a field that is constantly evolving and innovating. The application of these technologies enables the analysis of huge volumes of data, increasing the ability to discover complex patterns and generate insights that were previously hard to reach. Current trends focus on the adoption of more automated and efficient solutions such as AutoML, as well as improvements in tools and frameworks that facilitate integration on a broader level. While challenges such as interpretability and transparency remain, developments in explainable AI seek to address them. All of these advancements demonstrate the huge potential of AI and machine learning in transforming big data processing, providing significant benefits to various industry sectors through faster and more effective decision-making.